Caspian Vector of the EAEU Transport and Logistics Policy - I. B. Mamedov (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2021)
One of the goals of the Eurasian Economic Union is the formation of single markets for goods, services, capital and labor resources. A key aspect for the realization of the stated goal is the development of the EAEU transport and logistics potential. The formation of a single transport space, ensuring the free movement of goods and passenger traffic require an expansion of the EAEU participation in main international logistics projects, as well as the achievement of an agreed transport policy of member states. The purpose of this article is to determine the possibilities and limitations of interactions between the EAEU and Azerbaijan, Iran and Turkmenistan in the transport and logistics sphere. The article analyses the main directions and objectives of the EAEU transport policy, assesses the dynamics of the main indicators of the Union’s transport activities. The author considered key international transport projects for the EAEU. Logistics programs and corridors that pass through the territories of Azerbaijan, Iran and Turkmenistan are highlighted: the North-South international transport corridor, the EAEU and the Silk Road Economic Belt interface project, as well as the Central Asian regional economic cooperation programs and the Europe-Caucasus-Asia corridor project. The transit potential of the Caspian region in general and the territories of the represented countries in particular was studied. Analysis of the retrospective of relations of the EAEU with these countries is presented. The main result of the study is a description of promising areas of cooperation, individual projects and formats of cooperation in the transport and logistics sphere between the EAEU and the countries of the southern Caspian Sea. The author concludes that it is necessary to rehabilitate and reactualize the idea of the “Great Eurasian Partnership” in the light of the identified restrictions for the full integration of South Caspian countries into the EAEU.